Are Observed Capital Structures Determined by Equity Market Timing? - Hovakimian, Armen (Journal of Financial and Quantitative Analysis, 2006)
Abstract Contrary to Baker and Wurgler (2002), I find that the importance of historical average market-to-book ratios in leverage regressions is not due to past equity market timing. Although equity transactions may be timed to equity market conditions, they do not have significant long lasting effects on capital structure. Debt transactions exhibit timing patterns that are unlikely to induce a negative relation between market-to-book ratios and leverage. I also find that historical average market-to-book ratios have significant effects on current financing and investment decisions, implying that they contain information about growth opportunities not captured by current market-to-book ratios.